The fiscal footprint of macroprudential policy - Ricardo Reis (Deutsche Bundesbank, 2020)
Monetary policy leaves a fiscal footprint. In some circumstances, relieving the fiscal burden becomes the main goal of policy, and inflation control is subordinate. This article notes that the same is true of macroprudential policy, and it characterizes the size and sign of its fiscal footprint, as well as the states of the world in which the temptation for fiscal goals to dominate may be higher. Macroprudential policies that increase the demand for government bonds by banks directly lower the cost of rolling over public debt, but decrease lending, real activity, and tax collections. They lower the incidence and fiscal cost of a financial crisis, but they may make a fiscal crisis more likely.
Keywords: E58; E62; G01; G28; H63; 330; financial crisis; sovereign default; diabolic loop; capital and liquidity regulation